Pengalihan Kewenangan Tenaga Medis Kepada Beauty Therapist Dalam Praktik Klinik Kecantikan - Sampoerna, Ola Mehira (Faculty of Law, Universitas Airlangga, 2025)
This article discusses beauty clinics, which offer health services related to dermatology or the science of skin care. In today’s globalized era, many beauty clinics have emerged, particularly in Indonesia. This research investigates the delegation of authority that occurs in beauty clinics between medical professionals and beauty therapists who perform beauty treatments on clients. It also explores who is responsible for beauty treatments if any harm or unwanted consequences occur to the client. The research uses two approaches: a legal approach that examines relevant laws and a conceptual approach that studies the principles and doctrines used to address legal issues. The findings show that delegating authority from medical professionals to beauty therapists can be done, but specific regulations must be followed. Medical professionals are responsible for the delegated authority. However, if a beauty therapist performs actions beyond their delegated authority, they can be held accountable if their actions are negligent and harm the client. Delegation of authority may involve a transfer of responsibility from the medical professional to the beauty therapist. In this case, if the beauty therapist’s negligence causes harm to the client, they may be held criminally liable or liable according to the regulations governing their profession as a health worker